Social Caring Behavior of Elementary School Students in Interacting with Peers - Kurniawati; Wahyuningsih, Yona; Furnamasari, Yayang Furi; Rachmania, Setyaningsih (Journal of Islamic Communication and Counseling, 2023)
Childhood has an important role in human growth and development. For many people, character education is applied in the family, school, and community environment as an effort to instill positive character values in children, one of which is social care. This positive character emphasizes sympathy and empathy for those who need help. Instilling social care can be carried out by parents, teachers, and the community. Consequently, children interact daily with their peers as individuals and social beings. Children's interaction behavior is also influenced by the emotional and cognitive aspects that influence social care behavior in the form of attitudes and speech. Various symptoms in interacting with peers give rise to feelings of sympathy or antipathy towards appropriate and inappropriate behavior in the environment where children interact with peers, especially in the school environment. This study aims to describe the results of character analysis of social care behavior through descriptive qualitative methods with students at Panyileukan Elementary School, Kacapiring Elementary School, and Bhakti Nusantara Elementary School in Bandung. Forms of social care for children appear in the form of words, attitudes, and actions. Social concern in the form of greetings: asking about the condition/condition of friends, comforting friends who are feeling sad or in trouble, providing moral support to friends who are facing problems, and reprimanding/advising friends when friends make mistakes. Students' social concern is in the form of not being able to stay silent and not being able to accept a symptom that appears not in accordance with human and social norms. Actions carried out by students as a form of social care are providing assistance, protection, and mediating in times of conflict.